ABOUT SOME PECULIARITIES OF THE CONVERGENCE OF WESTERN AND EASTERN SYSTEMS OF EDUCATION IN THE CONDITIONS OF GLOBALIZATION - Ashilova, M. S.; Begalinova, K. K.; Begalinov, A. S. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2018)
The article deals with integration processes in the world educational system in the context of globalization. The objective nature of globalization, which enhances the communicative and informational connectivity of the world, is shown. Positive and negative aspects of the rapprochement of the western and eastern entities are analyzed. This convergence of different systems of entities will contribute to the growth of the socializing function of education and will become interethnic, integral. The article reveals the ontological content of such concepts as globalization and the internationalization of education in the context of the interconnection and differences of the eastern and western entities. The authors emphasize that at the present time there is a change of paradigms, education is qualitatively different. Its main goal is the transformation of a reasonable person into a consuming person, into an element of consumer information culture. What is the reason for this provision and how to stop this process, this will be discussed in this article. Key words: globalization, education, Western education, the eastern system of education, evolution, crisis, integration, education, knowledge-information, fundamentalization, humanization, humanitarization.